ARTISTIC AND EDUCATIONAL ROLE OF FAMILY MUSIC MAKING - Kataryńczuk-Mania, Lidia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Every family is influenced by modernity, transformation, various changes and the fast pace of life. Music can be the ideal basis for a modern family. The article will show scientific reflections on the educational and artistic role of creating family music. Goals and objectives, the specifics of music and building relationships in the environment of music will be emphasized.